Kredytowanie rolnictwa po akcesji do Unii Europejskiej na przykładzie banków spółdzielczych - Parvi, Rafał (Agriculture Crediting after the Accession to the European Union Presented on an Example of Collective Banks, 2005)
In the recent years one can observe the growth of collective banks assets, basically because economic subjects and individual farmers are running into debts. Such growth causes an increase of interest margins and income due to commission from loans charged by banks which contributes to increased profits of banks.After Poland's accession to the European Union different programmes are used. Within them development and modernization projects are financed. Financing agriculture modernization and development is gradual and very slow as it is connected with European Union's support.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 163-168